Alpha-1 Antitrypsin Deficiency Targeted Testing and Augmentation Therapy: A Canadian Thoracic Society Clinical Practice Guideline. Issue 2 (2012) - Marciniuk, DD; Hernandez, P; Balter, M; Bourbeau, J; Chapman, KR; Ford, GT; Lauzon, JL; Maltais, F; O'Donnell, DE; Goodridge, D; Strange, C; Cave, AJ; et al.
Abstract : Alpha-1 antitrypsin (A1AT) functions primarily to inhibit neutrophil elastase, and deficiency predisposes individuals to the development of chronic obstructive pulmonary disease (COPD). Severe A1AT deficiency occurs in one in 5000 to one in 5500 of the North American population. While the exact prevalence of A1AT deficiency in patients with diagnosed COPD is not known, results from small studies provide estimates of 1% to 5%. The present document updates a previous Canadian Thoracic Society position statement from 2001, and was initiated because of lack of consensus and understanding of appropriate patients suitable for targeted testing for A1AT deficiency, and for the use of A1AT augmentation therapy. Using revised guideline development methodology, the present clinical practice guideline document systematically reviews the published literature and provides an evidence-based update. The evidence supports the practice that targeted testing for A1AT deficiency be considered in individuals with COPD diagnosed before 65 years of age or with a smoking history of <20 pack years. The evidence also supports consideration of A1AT augmentation therapy in nonsmoking or exsmoking patients with COPD (forced expiratory volume in 1 s of 25% to 80% predicted) attributable to emphysema and documented A1AT deficiency (level ≤11 μmol/L) who are receiving optimal pharmacological and nonpharmacological therapies (including comprehensive case management and pulmonary rehabilitation) because of benefits in computed tomography scan lung density and mortality. Erratum to "Alpha-1 Antitrypsin Deficiency Targeted Testing and Augmentation Therapy: A Canadian Thoracic Society Clinical Practice Guideline" dx.doi.org/10.1155/2012/130891